2021
DOI: 10.1016/j.cogsc.2021.100476
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the stereoselective synthesis of (poly)-substituted 2-oxo acids by biocatalyzed aldol reaction

Abstract: Recently, an increased interest toward enzymatic carboligation was observed, as biocatalytic carbon–carbon bond formation is a common obstacle in retrosynthetic planning. The construction of extended 2-oxoacid frameworks by 2-oxoacid aldolases and enzymes acting as aldolases is a potent tool for synthetic chemists since a broad spectrum of downstream reactions through functional group interconversions gives access to a plethora of compound classes. In the search for selective biocatalysts, successful protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Nonetheless, the molecular dockings were performed and showed that N -benzyloxycarbonyl ( N -Cbz)-substituted aldehydes are surrounded by hydrophobic residues Trp23, Phe174, and Leu216, similar to the aldehyde binding residues identified in Ab HpaI. These properties offer an opportunity for Ab HpaI to serve as a biocatalyst to catalyze formation of 4-hydroxy-2-ketoacid and 2-keto-3-deoxy-D-sugar acid precursors valuable for the synthesis of APIs ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the molecular dockings were performed and showed that N -benzyloxycarbonyl ( N -Cbz)-substituted aldehydes are surrounded by hydrophobic residues Trp23, Phe174, and Leu216, similar to the aldehyde binding residues identified in Ab HpaI. These properties offer an opportunity for Ab HpaI to serve as a biocatalyst to catalyze formation of 4-hydroxy-2-ketoacid and 2-keto-3-deoxy-D-sugar acid precursors valuable for the synthesis of APIs ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 93%
“…In accordance with literature. [13] [(S)-5-(Benzyloxy)-4-hydroxypentan-2-one] (3 b) 207 mg isolated yield (62%), 87% ee, colorless oil. Chiral HPLC t R (R) = 16.2 min; t R (S) = 19.5 min.…”
Section: Synthesis Of Aldol Products With Nucleophile 2 Cmentioning
confidence: 99%
“…mg isolated yield (56%), 79% de, yellow liquid 1 H NMR (300 MHz, d 4 -MeOH): Major: δ 7.37-7.25 (m, 5H), 4.54 (s, 2H), 3.88 (ddd, J = 9.6, 5.5, 4.4 Hz, 1H), 3.41 (d, J = 5.4 Hz, 2H), 3.21 (q, J = 6.5 Hz, 1H), 1.62-1.53 (m, 2H), 1.17 (d, J = 6.5 Hz, 3H). J = 6.5 Hz, 3H) 13. C NMR (75 MHz, d 4 -MeOH): Major: δ 139.6, 129.4, 128.9, 128.7, 75.9, 74.4, 70.3, 41.8, 22.1.…”
mentioning
confidence: 99%
“…Enzymes from the aldolase family catalyze aldol reactions, which intriguingly set up a chiral alcohol center with concomitant C–C bond formation. Examples for processes include the formation of the side chains of statins or hydroxy-amino acids (section ). , In a similar fashion, thiamine diphosphate (ThDP)-dependent enzymes form acyloin-type compounds (section ).…”
Section: Functional Groups Formed In Biocatalytic Reactions For Api S...mentioning
confidence: 99%